Clinico-laboratory correlation with outcome in Paediatric Intensive Care Unit of Western Nepal - BK, Ganesh; Gauchan, Eva; Timilsina, Mukunda (Journal of Karnali Academy of Health Sciences, 2022)
Background: Intensive care has become an important part of the management of critically ill children. These patients need better care and management for good outcomes. The objective of this study is to identify the clinical and laboratory characteristics which can influence on the outcome of patients, morbidities and mortality and help in the improvement of the quality of care to the child. Methods: This is a prospective study conducted over a period of 6 months from January 2018 to June 2018 in the PICU. Children admitted in PICU in the age range of one month to fifteen years were enrolled after taking consent from the parents’ Results: The majority of the patients (23 each in the group) belong to the age group of 1 month to 1 year. The most common systemic presentations were respiratory 38(38%), neurological 24(24%), gastrointestinal 9(9%), and poisoning 9(9%). Serum Urea level of 48.46±4.61 mg/dl and creatinine level of 1.27±1.48 mg/dl in poor outcome group was found to be significantly greater than urea level of 33.98±2.58 mg/dl and creatinine level of 0.84±0.242 mg/dl in good outcome group with a p-value of 0.0001 and 0.0453 and Conclusion: Most of the children were of age <5 years. High total count shows a significant association with the poor outcome compared to other laboratory parameters. Patients in the poor outcome group presented with higher total counts, serum urea, and creatinine levels than those in the good outcome group. Hospital stay was longer in the good outcome group compared to the poor outcome group.